COMPLEMENTARY FEEDING KNOWLEDGE AND ITS RELATED FACTOR ON COVID-19 POST PANDEMIC (Proceedings of the Global Public Health Conference, 2022)
Inappropriate complementary feeding (CF) is a major cause of child malnutrition and is more difficult when the COVID-19 (coronavirus disease-2019) occurs in Indonesia. The COVID-19 pandemic has made changes to healthcare utilization. This study purposed to capture and see the determinants of the mothers' CF knowledge during the COVID-19 pandemic. It focused on 133 mothers who have children aged 6-24 months and have internet access. The study was a cross-sectional and observational study conducted in Depok, West Java, Indonesia. The online survey for four weeks (November-December 2021) was performed to assess mothers' knowledge regarding CF during the COVID-19 outbreak. The obtained data were analyzed using logistic regression against various parameters, including mothers' education, knowledge, etc. The results exhibited that most mothers were 20-40 years old and had a bachelor's degree. Among the studied population, knowledge level on CF practice during the COVID-19 was fairly acceptable even though 53.4% of mothers had never gone to maternal class during the pandemic. Maternal education was the strongest determinant of CF knowledge (p= 0.009), even during the outbreak. Next, the research revealed that the maternal class did not directly affect CF knowledge during the COVID-19. On the other hand, health workers' role was one of the strongest CF determinants (p= 0.01). In conclusion, even though it is crucial to have good awareness about CF, it is strongly recommended that healthcare keep improving their CF online consultation and health social media as a reliable source, especially during the pandemic.
Keywords: mother; knowledge; complementary feeding; COVID-19; health promotion; health education